(untitled) (Journal of Geography and Environmental Management, 2017)
Question mono-cities is not only a problem of one region but for the whole of the Republic. The problem is not only in the fact that 17% of the population lives in these cities, but these cities can contribute to the development of the country. Sometimes these are called single-industry town, because the town specialize in the production of a narrow range. For these cities is essential operation of large industrial enterprises. Kazakhstan 27 mono-cities, 1.53 million people live in these cities. The reasons that led to the destruction of one-company towns: the destruction of infrastructure, the rapid rise in unemployment, the degradation of social life. Reduction of raw materials in single-industry towns has led to many problems. In connection with this company towns have been targets of economic collapse and social crisis. At present, another problem of monotowns is the migration of the population. Preservation of jobs, health, infrastructure development is one of the most important goals for the development of single-industry towns. The article uses statistical data and describes important problems of monotowns in Central Kazakhstan and identifies problems.